1998
DOI: 10.1164/ajrccm.157.5.9710017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Gastric Mucosal Oxygenation in Septic Shock

Abstract: Splanchnic mucosal perfusion abnormalities have been implicated in the development of sepsis and multiorgan failure. We employed reflectance spectrophotometry for direct assessment of the microvascular hemoglobin oxygen saturation (HbiO2) and hemoglobin concentration (rel Hb(conc)) in the mucosa of the upper gastrointestinal tract. Owing to the high recording frequency together with a small catchment volume, assessment of spatial heterogeneity is enabled. Results were as follows: In healthy controls (n = 7), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(75 citation statements)
references
References 31 publications
0
68
1
6
Order By: Relevance
“…By injecting black ink into different layers of the intestinal wall, they demonstrated that the catchment volume of spectrophotometric data was limited to mucosal and, to a lesser degree, to submucosal vessels. In previous studies, we and others have hypothesized that measurements of HBjO 2 are limited to the mucosal and probably submucosal layer of the intestinal wall (8,13,27). However, in a recent investigation, we were able to demonstrate that the light emitted by the eluminating microlightguide penetrates the whole intestinal wall and is reflected by a mirror intermittently placed under the preparation resulting in an increase in light intensity detected by the photomultiplier tube (25).…”
Section: Discussionmentioning
confidence: 75%
“…By injecting black ink into different layers of the intestinal wall, they demonstrated that the catchment volume of spectrophotometric data was limited to mucosal and, to a lesser degree, to submucosal vessels. In previous studies, we and others have hypothesized that measurements of HBjO 2 are limited to the mucosal and probably submucosal layer of the intestinal wall (8,13,27). However, in a recent investigation, we were able to demonstrate that the light emitted by the eluminating microlightguide penetrates the whole intestinal wall and is reflected by a mirror intermittently placed under the preparation resulting in an increase in light intensity detected by the photomultiplier tube (25).…”
Section: Discussionmentioning
confidence: 75%
“…However, though dopexamine infusion was associated with a partial correction of spectrophotometric gastric Hbi O2 , pCO 2 g-a remained unaltered [76]. This might be compatible with persistence of microcirculatory weak units Increase of urine output and creatinine clearance, rise in bilirubin, no significant change in pCO 2 g-a AVP Argenine vasopressin, OPS orthogonal polarization spectral, pCO 2 g-a arterial-to-gastric pCO 2 gradient, MAP mean arterial pressure, EDTA ethylenediaminetetraacetic acid in combination with shunting, not sensed by spectrophotometry due to incorporation of arteriolar and venular hemoglobin.…”
Section: Vasopressorsmentioning
confidence: 92%
“…The flexible light-guide probe introduced into the stomach is positioned facing the greater curvature (Scheeren et al 2002), a site demonstrated to represent the microvascular oxygenation of other gastric and upper intestinal mucosa regions (Temmesfeld-Wollbruck et al 1998). Online evaluation of the signal quality throughout the experiments allows verification of the correct position of the probe tip.…”
Section: Measurementsmentioning
confidence: 99%